Cloud Enabled e-glossary System: A Smart Campus Perspective - Al-Nadwi, Musaddiq Majid Khan; Refat, Nadia; Zaman, Nafees; Rahman, Md. Arafatur; Bhuiyan, Md Zakirul Alam; Ramdan, Razali (Springer, 2018)
Smart campus is a recent idea in the development of information and communication technology, being a combination of cloud computing, Internet of Things (IoT) and other emerging technologies. This paper demonstrates the result of our research efforts using IoT technology for the development of a smart campus, which also assures the improvement of vocabulary knowledge of the students. Our proposed system is mainly based on e-learning which provides definition of words and how to use that word in a sentence. However, students can take part in it and add more vocabularies in this glossary system under supervision through cloud computing. The quantitative research method is applied to validate the proposed system that provides the positive outcome. Therefore, it is an important research finding for vocabulary learning that can contribute to the building of smart campus exploiting the e-learning technologies.